Caracterização e aprimoramento do antimoniato de meglumina visando um tratamento eficaz e seguro da leishmaniose - Henrique José Ferraz Fabrino (2021)
Meglumine antimoniate (MA) is a pentavalent antimony (SbV) drug recommended for the treatment of leishmaniasis. It is known that the trivalent antimony (SbIII) present as a residue in MA contributes to the drug side effects and to the development of antimonial drug resistance. In this work, design of experiments (DOE) was used in the synthesis of MA in order to obtain a drug with low levels of SbIII. Four variables (source of SbV, volume, temperature, water volume and pH) and their interactions were preliminarily evaluated by 24-1 fractional factorial design. Central composite design (CCD) was used to determine the optimal conditions of two synthetic routes, using different sources of SbV. The analysis of MA formulations synthesized under optimized conditions revealed the efficiency of DOE to reduce SbIII content. In addition, the monitoring of some physicochemical parameters, i.e., SbIII content, pH and osmolarity of these formulations maintained at 40 oC for 90 days, showed that stability was not altered at 95% confidence. The SbIII content, in relation to the amount of total Sb, present in MA compounds was used as a response in the DOE and in the evaluation of the MA formulations stability. For this purposte, a procedure for speciation of inorganic Sb in MA was developed and validated using hydride generation atomic absorption spectrometry (HG-AAS). The Sb speciation occurs in two stages: 1) quantification of total Sb using a reducing agent (KI); 2) quantification of SbIII by the selective generation of stibin (SbH3) with the use of citric acid, in medium with higher SbV concentration. The concentration of citric acid used in the optimized method was 4 to 20-fold lower than that recommended in the literature, preventing clogging of the capillary of the T quartz cell. The limits of quantification (LOQ) were calculated at 0.48 μg L-1 for total Sb and 0.17 μg L-1 for SbIII. The relative standard deviation (RSD) values ranged from 3.1 to 19.6% and 9.1 to 20.1%, while recovery ranged from 95.6 to 102.3% and 89.1 to 108.1%, for total Sb and SbIII, respectively.